2000
DOI: 10.1021/ac991181u
|View full text |Cite
|
Sign up to set email alerts
|

A MALDI Sample Preparation Method Suitable for Insoluble Polymers

Abstract: Polyamides are insoluble or poorly soluble in common organic solvents, which makes normal sample preparation for matrix-assisted laser desorption/ionization (MALDI) mass spectrometry very difficult. An new analytical protocol for MALDI analysis of polyamides or other insoluble samples is described. It consists of pressing a pellet from a solid mixture of the polymer and a matrix, both in the form of finely ground powder. This sample preparation is compared with the common dried droplet sample preparation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
125
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 18 publications
1
125
0
Order By: Relevance
“…As a result, prediction for the optimal matrix-polymer system is still not possible and sample preparation methods are usually developed from published protocols that were shown to work for a given polymeric system [3]. In particular, solvent-free MALDI was recently proposed as an alternative to the conventional dried droplet method [4,5].Despite MALDI being a widely used technique, mechanisms underlying this desorption/ionization process are still not fully understood. To investigate the MALDI process, many studies have focused on sample morphology using different imaging experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, prediction for the optimal matrix-polymer system is still not possible and sample preparation methods are usually developed from published protocols that were shown to work for a given polymeric system [3]. In particular, solvent-free MALDI was recently proposed as an alternative to the conventional dried droplet method [4,5].Despite MALDI being a widely used technique, mechanisms underlying this desorption/ionization process are still not fully understood. To investigate the MALDI process, many studies have focused on sample morphology using different imaging experiments.…”
mentioning
confidence: 99%
“…As a result, prediction for the optimal matrix-polymer system is still not possible and sample preparation methods are usually developed from published protocols that were shown to work for a given polymeric system [3]. In particular, solvent-free MALDI was recently proposed as an alternative to the conventional dried droplet method [4,5].…”
mentioning
confidence: 99%
“…Many interesting polymeric analytes are either completely insoluble or present significant challenges in making analytically useful solutions. To address these issues, solvent-free sample preparation methods have been developed [11][12][13][14][15]. Previous papers have demonstrated that solvent free sample preparations can produce analytically useful polymer MALDI data for insoluble analytes.…”
mentioning
confidence: 99%
“…These are grinding by mortar and pestle [4,5], ball-mill [1][2][3][4], and vortexing [6]. Analyte, matrix, and salt are added to a vessel and, in the case of the ball-mill or vortex methods, suitably sized balls are used to assist in the homogenization process.…”
mentioning
confidence: 99%
“…Two general methods exist for the dry transfer of the homogenized powder from the vessel to the MALDI plate. In one method a pressed pellet is affixed to the plate with double-sided adhesive tape [5] and in another a loose powder [1][2][3][4] is transferred by the use of a small spatula, gently pressing it to the plate and producing a thin film.…”
mentioning
confidence: 99%